2019
DOI: 10.1186/s12943-019-1018-y
|View full text |Cite
|
Sign up to set email alerts
|

Function and clinical relevance of RHAMM isoforms in pancreatic tumor progression

Abstract: The receptor for hyaluronic acid-mediated motility (RHAMM) is upregulated in various cancers. We previously screened genes upregulated in human hepatocellular carcinomas for their metastatic function in a mouse model of pancreatic neuroendocrine tumor (PNET) and identified that human RHAMM B promoted liver metastasis. It was unknown whether RHAMM B is upregulated in pancreatic cancer or contributes to its progression. In this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“… 122 125 Upon HA binding, both CD44 and RHAMM function as a co‐receptors to activate other transmembrane tyrosine kinases, including epidermal growth factor receptor, c‐MET, and platelet‐derived growth factor receptor to promote tumor progression and therapeutic resistance. 117 , 126 , 127 In addition, CD44 and RHAMM ligation also activates kinases including ERK, FAK, Src to promote cell migration, invasion, and survival. 118 , 128 – 130 Importantly, downstream signaling and functional output of CD44 ligation is greatly dependent on the molecular weight of bound HA.…”
Section: Components Of Pdac Tumor Microenvironment (Tme) That Drive Ementioning
confidence: 99%
“… 122 125 Upon HA binding, both CD44 and RHAMM function as a co‐receptors to activate other transmembrane tyrosine kinases, including epidermal growth factor receptor, c‐MET, and platelet‐derived growth factor receptor to promote tumor progression and therapeutic resistance. 117 , 126 , 127 In addition, CD44 and RHAMM ligation also activates kinases including ERK, FAK, Src to promote cell migration, invasion, and survival. 118 , 128 – 130 Importantly, downstream signaling and functional output of CD44 ligation is greatly dependent on the molecular weight of bound HA.…”
Section: Components Of Pdac Tumor Microenvironment (Tme) That Drive Ementioning
confidence: 99%
“…RHAMM is not expressed in normal adult pancreas and its expression is restricted in other normal adult human tissues (98). Our studies showed that RHAMM B is overexpressed in human primary PNETs and liver metastases and it is a key driver for liver metastasis of PNET in mouse models (99). Therefore, RHAMM B could be a potential therapeutic target in PNETs.…”
Section: Molecular Characterization Of Pnetsmentioning
confidence: 79%
“…The main reason is that the number of patients tested by immunohistochemistry is too small, just only 35 patients (26). Although this is the first study to show that HMMR expression could be a prognostic factor for HNSCC, a large number of relevant studies have revealed that HMMR expression could be an adverse prognostic biomarker for various tumors (14)(15)(16)(17)(18). Considering that HMMR is a strong prognostic factor, we constructed a nomogram combining the HMMR expression and clinical data.…”
Section: Discussionmentioning
confidence: 99%